2021
DOI: 10.2147/jbm.s291226
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Neutrophil Lymphocyte Ratio and D-Dimer as Biological Markers of Deep Vein Thrombosis in Patients Presenting with Unilateral Limb Edema

Abstract: Introduction: Patients with deep vein thrombosis (DVT) pose high morbidity and mortality risk thus needing fast and accurate diagnosis. Wells clinical prediction scores with D-dimer testing are traditionally used to rule out patients with low probability of DVT. However, D-dimer testing has a few limitations regarding its relatively low specificity. Neutrophillymphocyte ratio (NLR), a marker of inflammation, was found to increase in DVT. Hence, we aimed to evaluate the role of NLR for DVT diagnosis. Methods: D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 37 publications
(94 reference statements)
1
11
0
Order By: Relevance
“…Similar results were reported by Erden et al with an AUC of 0.739, a sensitivity of 72%, and a specificity of 67% at an NLR cut-off value of 2.12. Other studies by Farah et al [ 17 ], Mouabbi et al [ 18 ], Rinaldi et al [ 19 ], Tural et al [ 16 ], and Sujana et al [ 20 ] also reported similar results. On ROC analysis of PLR, we found out that the AUC for PLR was 0.746.…”
Section: Discussionsupporting
confidence: 66%
“…Similar results were reported by Erden et al with an AUC of 0.739, a sensitivity of 72%, and a specificity of 67% at an NLR cut-off value of 2.12. Other studies by Farah et al [ 17 ], Mouabbi et al [ 18 ], Rinaldi et al [ 19 ], Tural et al [ 16 ], and Sujana et al [ 20 ] also reported similar results. On ROC analysis of PLR, we found out that the AUC for PLR was 0.746.…”
Section: Discussionsupporting
confidence: 66%
“…Rinaldi et al have compared the diagnostic power of NLR and D-dimer for predicting DVT. 25 In this study, NLR had higher sensitivity than D-dimer (65% vs 60%) in patients with a low probability of DVT. Furthermore, for patients with a high probability of DVT, NLR had higher specificity than D-dimer (69.2% vs 53.8%).…”
Section: Discussionmentioning
confidence: 50%
“…Eventually, 10 articles with 1513 VTE participants and 2593 control participants were included for quantitative synthesis. [17][18][19][20][21][22][23][24][25][26] Table 1 and Table 2 illustrate the characteristics of included studies. All were retrospective case-control studies.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…In this context, hematologic ratios such as neutrophil-to-lymphocyte ratio (NLR), derived NLR (d-NLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) represent inflammatory markers that have already been described as diagnostic auxiliars for the diagnosis and prognosis of other diseases. [3][4][5][6] Novel data suggest that NLR is associated with various inflammatory conditions even with subtle or overt inflammation which includes diabetes mellitus, irritable bowel disease, and thyroiditis. [7][8][9] It is even associated with COVID-19 disease.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, hematologic ratisos such as neutrophil-to-lymphocyte ratio (NLR), derived NLR (d-NLR), lymphocyte-to-monocyte ratio (LMR), platelet-to-lymphocyte ratio (PLR), and systemic immune-inflammation index (SII) represent inflammatory markers that have already been described as diagnostic auxiliars for the diagnosis and prognosis of other diseases. 36…”
Section: Introductionmentioning
confidence: 99%